2011
DOI: 10.2340/00015555-1086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Narrow-band Ultraviolet B Phototherapy on p63 and MicroRNA (miR-21 and miR-125b) Expression in Psoriatic Epidermis

Abstract: Psoriasis is an inflammatory skin disease in which dysregulation of p63, a member of the p53 family that is crucial for skin development and maintenance, has been demonstrated. Involvement of miR-203, miR-21 and miR-125b, small non-coding RNAs implicated in the regulation of p63 or p53, has been suggested in the patho-genesis of psoriasis. To elucidate the roles of p63 and p63-related microRNAs in psoriasis and to increase our understanding of the mechanisms of narrow-band ultraviolet B (NB-UVB) phototherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…In this study, q-PCR showed high degrees of sensitivity and accuracy for measuring the expression of these genes. Immunohistochemistry has confirmed the PCR results on the protein level, showing that these methods are similar to previous dermatological studies [12,13,16]. mRNA levels and protein expression corresponded in our current study.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, q-PCR showed high degrees of sensitivity and accuracy for measuring the expression of these genes. Immunohistochemistry has confirmed the PCR results on the protein level, showing that these methods are similar to previous dermatological studies [12,13,16]. mRNA levels and protein expression corresponded in our current study.…”
Section: Discussionsupporting
confidence: 92%
“…Also there was decrease in miR146a level in patients treated with NB-UVB in this study; this was in accordance with the results of Gu et al [ 24 ]. This was due to the effect of NB-UVB leading to cell cycle arrest, T cell apoptosis, and apoptosis upon DNA damage as stated by Menter et al [ 25 ] and Gu et al [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…[41] Our results clearly showed expression of all three miRNAs studied to be altered in tumor tissue compared to clinically normal tissue from the same patients. In accordance with previous studies, miR-21 was significantly upregulated in tumors compared to control samples, whereas miR-125b and miR-203 showed significantly decreased expression in tumor samples compared to controls, indicative of a role for all these miRNAs in this tumor type.…”
Section: Discussionmentioning
confidence: 65%